'n Hoofstuk in die (outo)biografie van die predikant (pastor?) - J-A. van den Berg (Acta Theologica)
This article makes a further contribution (chapter) to the existing debate (book) about the office, personality and spirituality of the pastor. Voices from literature, those of various pastors (biographical) and that of the author (autobiographical) direct the process of Participatory Action Research and supply the text. From various stories it becomes clear that the pastor is under pressure. Until now research was aimed on the one hand at indicating why pastors are under pressure and on the other hand how the causes can be managed. The sub-text speaks for the approach in this article when it is indicated that the acknowledgement of pain does not only give new meaning to the self, but to the pastoral duty as well. The development of the metaphor “wounded healer” and the associative networks it awakens, are important in the establishment of these accents in a new life text. This perspective ought to be articulated in the further development of metaphors for the description of the identity of the pastor.